The role of values in collaborative consumption: insights from a product-service system for lending and borrowing in the UK. (15th June 2015) - Piscicelli, Laura; Cooper, Tim; Fisher, Tom
Abstract: Collaborative consumption is an emerging socio-economic model based on sharing, renting, gifting, bartering, swapping, lending and borrowing. Made possible through community interaction and, increasingly, use of network technologies, these alternative and more sustainable ways of consuming have attracted growing attention for their potential to prevent new purchases, intensify the use of idle assets and promote reuse of possessions that are no longer wanted. Nonetheless, the uptake of Product-Service Systems (PSSs) that enable collaborative consumption is still very limited. This paper investigates how consumers' values can influence the acceptance, adoption and diffusion of collaborative consumption. It reviews two theoretical frameworks used to understand pro-environmental behaviour, social psychological models of behaviour and social practice theory. Coming from contrasting disciplinary perspectives, these approaches conceptualise values differently. The paper evaluates the possibility of resolving these differences through a mixed methods study. It examines values empirically through a case study of Ecomodo, a UK-based online marketplace where people can lend and borrow each other's objects, spaces and skills, and present the results of a quantitative study which identified and measured value priorities among Ecomodo users through Schwartz's Portrait Value Questionnaire. It concludes with a discussion of the role of values in relation to the introduction and scaling up of PSSs that enable collaborative consumption. Highlights: A case study of an on-line marketplace for peer-to-peer sharing is presented. Consumers' values are salient to their involvement in collaborative consumption. It is possible to reconcile social psychology and social practice theory by linking values and meaning. The role of values in relation to the introduction and scaling up of PSSs is discussed.